NEW PROSPECTS OF WALNUT LEAF AND MULBERRY LEAF EXTRACTS IN ONCOLOGICAL THERAPY (International journal of medical sciences, 2025)
In this study, the therapeutic significance of natural bioactive compounds isolated from the leaves of Juglans regia L. (walnut) and Morus alba L. (mulberry) in oncological processes was analyzed. The results demonstrated that the phenolic acids, flavonoids, and antioxidant components present in walnut leaf and mulberry leaf extracts may restrict the metabolic activity of cancer cells. Additionally, the obtained findings suggest that plant-derived natural compounds can serve as a promising direction for the development of oncoimmunotherapeutic and antiangiogenic agents.